Prevalence of adverse drug events and adverse drug reactions in hospital among older patients with dementia: A systematic review. Issue 2 (6th July 2020) - Sakiris, Marissa Anne; Sawan, Mouna; Hilmer, Sarah Nicole; Awadalla, Rebecca; Gnjidic, Danijela
Abstract : Aims: This systematic review aimed to quantify the prevalence of adverse drug events (ADEs) and adverse drug reactions (ADRs) in older inpatients with dementia. Methods: A systematic search of observational studies was performed in Embase, Medline, PsycINFO, International Pharmaceutical Abstracts, Scopus and Informit. Articles published in English that reported the prevalence of ADEs or ADRs in hospital patients aged 65 years or older with dementia were included. Two authors reviewed titles and abstracts and all eligible full‐text articles. Relevant information relating to ADEs, ADRs and dementia was obtained from each article. Results: In total, 5 articles were included. One study reported the prevalence of ADEs to be 81.5%, defined using the Naranjo algorithm. Four studies assessed the prevalence of ADRs, ranging from 12.7 to 24.0%, assessed using various methods. One study defined ADRs according to the World Health Organization‐Uppsala Monitoring Centre criteria, 2 studies employed the World Health Organization definition and 1 study did not explicitly define ADRs. The most frequently reported drug classes implicated in ADEs and ADRs were psychotropic, antihypertensive and analgesic drugs. Conclusion: Our findings suggest a high prevalence of ADEs and ADRs in older inpatients with dementia. However, only 1 study documented ADEs and there was variability in approaches to ADR assessment. A greater understanding of ADEs and ADRs, as well as tailored assessment tools, will promote prevention of ADEs and ADRs in people with dementia.